Dynamic change in respiratory resistance during inspiratory and expiratory phases of tidal breathing in patients with chronic obstructive pulmonary disease - Yamauchi, Yasuhiro (Dove Medical Press, 2012)
BACKGROUND AND OBJECTIVE: Chronic obstructive pulmonary disease (COPD) is characterized by persistent airflow limitation consisting of airway obstruction and parenchymal emphysema, with loss of elastic recoil. The forced oscillation technique can detect impairment of lung function by measuring lung impedance during normal tidal breathing. Respiratory resistance (Rrs) in COPD has been well-studied, but the differences in Rrs in the inspiratory and expiratory phases between mild and moderate COPD remain poorly understood. Since airway obstruction in COPD is known to change dynamically during tidal breathing and might affect Rrs, the differences in Rrs during tidal breathing between mild and moderate COPD were evaluated. METHODS: Mild (n = 13) and moderate (n = 13) COPD patients were recruited at Tokyo University Hospital (Tokyo, Japan). Rrs was measured using MostGraph-01 (Chest MI, Inc, Tokyo, Japan), which depicted Rrs in a frequency-and respiratory cycle-dependent manner in three-dimensional graphics. Rrs was evaluated at 4–35 Hz during tidal breathing. RESULTS: Rrs changed dynamically during tidal breathing in COPD. The mean Rrs values were significantly greater in the moderate COPD group than in the mild group. The maximal and minimal Rrs values at higher frequencies in the respiratory cycle were significantly greater in moderate COPD. In inspiratory–expiratory breath analysis, the maximal and minimal Rrs values at 20 Hz and 35 Hz were significantly greater in the moderate group, whereas at 4 Hz they did not differ significantly between the groups. CONCLUSION: Rrs changed dynamically during tidal breathing in patients with COPD. The Rrs values at higher frequencies were greater in moderate COPD than in mild COPD. Rrs at higher frequencies might reflect the degree of airway obstruction in tidal breathing in patients with COPD and might be a useful marker for evaluation of airway obstruction at an early stage of COPD.